A core-shell Au@Cu2-xSe heterogeneous metal nanocomposite for photoacoustic and computed tomography dual-imaging-guided photothermal boosted chemodynamic therapy - Zhang, Le; Jiang, Chunjuan; Li, Bing; Liu, Zhengwang; Gu, Bingxin; He, Simin; Li, Panli; Sun, Yun; Song, Shaoli (Journal of nanobiotechnology, 2021)
Chemodynamic therapy (CDT) has aroused extensive attention for conquering cancers because of its high specificity and low invasiveness. Quick generation of hydroxyl radicals ( · OH) during CDT could induce more irreparable damage to cancer cells. The generation rate of · OH could be magnified via the selection of suitable nanocatalysts or under the assistance of exogenous thermal energy from photothermal therapy (PTT). Here, we construct a kind of monodisperse core-shell Au@Cu 2-x Se heterogeneous metal nanoparticles (NPs) for PTT boosted CDT synergistic therapy. Due to the localized surface plasmon resonance (LSPR) coupling effect in the core-shell structure, the photothermal conversion efficiency of Au@Cu 2-x Se NPs is up to 56.6%. The in situ generated heat from photothermal can then accelerate the Fenton-like reaction at Cu + sites to produce abundant · OH, which will induce apoptotic cell death by attacking DNA, contributing to a heat-boosted CDT. Both in vitro and in vivo results showed that after this synergistic therapy, tumors could be remarkably suppressed. Guided by photoacoustic (PA) and computed tomography (CT) imaging, the therapeutic effects were more specified. Our results revealed that PA and CT dual-imaging-guided PTT boosted CDT synergistic therapy based on core-shell Au@Cu 2-x Se NPs is an effective cancer treatment strategy. Graphical Abstract